Comparison of cutting speed variations in the laser cutting process on the results of SS400 steel plate products - Amalia, Mutia; Purba , Adi Syahputra; Rafly, Stevian; Cuana, Rona; Ritonga, Fatima Sari (International Journal of Mechanical Computational and Manufacturing Research, 2025)
Computer Numerical Control (CNC) laser cutting as a manufacturing tool for plate cutting, where industrial players are encouraged to get maximum results. Laser cutting is one of the tools used by the industrial world to maximize cutting results. The aim of this research is to determine the results of differences using cutting speed parameters on SS400 steel plate with a thickness of 1 mm using CNC fiber laser cutting on the surface roughness of the material. The method used in this research is a real experimental research method and data analysis to analyze the parameters of cutting plates using laser cutting on surface roughness with the number of experiments being replicated 2 times for the research process by testing surface roughness using Surface Roughness.